An occupational risk assessment approach for construction and operation period of wind turbines - M. Gul; A.F. Guneri; M. Baskan (Global Journal of Environmental Science and Management)
As wind energy is one of the most important renewable energy sources over the globe, need for increasing safety for this type of energy is gaining importance. Although this sector is not suffering an excessive amount of fatal injury accidents, there are many aspects open for improvements in occupational health and safety management. The construction and operation processes of wind turbines include several hazards that must be reduced. This study aims to present a risk assessment for the construction and operation period of wind tribunes using a new fuzzy based method. Fuzzy analytical hierarchy process, a common used multi criteria decision making method, is applied to assign weights to the parameters of Fine-Kinney risk analysis method. Then, fuzzy VIKOR method is used to prioritize hazards. A case study is carried out for an onshore wind turbine in Turkey by using occupational health and safety experts in weighting risk parameters and evaluating compromised rankings of the hazards. Results reveal the most important hazards both for construction and operation period of the wind tribune. On conclusion of the current study, control measures for those risks and possible corrective-preventive actions for improvement are also provided.